System of observation of day-time asteroids (SODA) - Shugarov Andrey; Shustov Boris; Naroenkov Sergey (Open Astronomy, 2018)
Chelyabinsk event of Feb 15, 2013 clearly demonstrated that decameter sizeNear EarthObjects (NEO) should be considered as hazardous ones. Another important lesson is that bodies approaching the Earth from day sky could not be discovered by any ground-based or near Earth space telescopes and the only way to detect these bodies reasonably well beforehand is to put the telescope(s) relatively far fromthe Earth.We proposed the project of space system SODA (System of Observation of Day-time Asteroids) for exhaustive detection of decameter (and larger) bodies approaching the Earth from the Sun direction (Chelyabinsk type meteoroids). The medium-size (30 cm) wide field telescopes are to be put into vicinity of L1 (Earth-Sun) point. Observations will be performed in barrier mode. Two options are considered: single spacecraft (SC) or pair of SCs. We describe major constituents and options of the project. The entire project could be implemented with off-shelf components and fits to low-cost project requirements. Special attention is paid to accuracy of orbit of the NEO. In a variant of two SCs capable to perform observation in triangulation mode accuracy of atmosphere entry point for Chelyabinsk-like body could be as high as few tens of kilometers.